Microstructure-property correlations in as-built and heat-treated compositionally graded stainless steel 316L-Inconel 718 alloy fabricated by laser powder bed fusion - Wen, Yaojie (2023)
The microstructures and the mechanical properties of a laser powder bed fusion manufactured compositionally graded alloy of the austenitic stainless steel 316L and Inconel 718, in the as-built and heat-treated conditions, were investigated. In all the cross sections of the as-built compositionally graded alloy, along the compositional gradient direction, which is perpendicular to the build direction, the microstructure primarily consists of sub-micron sized cells embedded within <001> textured columnar grains of the γ phase along with Laves phases at their grain boundaries. Heat treatment, which involves solutionizing at 1040 °C for 1 h followed by annealing at 720 °C and 620 °C for 10 h each, leads to coarsening of Laves phases, slight modification in texture and the annihilation of the sub-grain structure of the compositionally graded alloy, but does not alter the columnar grain size. It also leads to precipitation of the γ" and γ' phases in the portions of the compositionally graded alloy with >70 wt% of IN718. The hardness, yield strength and tensile strength of the compositionally graded alloy increase but ductility decreases from the SS316L-rich end to the IN718-rich end along the gradient direction. Heat treatment smoothens the variations in YS and UTS along the gradient direction in cross sections with <82 wt% IN718 but reduces their relative magnitude compared to that of the as-built condition. The heat-treated compositionally graded alloy exhibits significantly higher YS and UTS but lower ductility than that in the as-built condition, in portions with ≥82 wt% IN718. These mechanical property variations are analyzed in detail by considering variations in the composition, microstructural features, and contents of different phases in the as-built and heat-treated compositionally graded alloy. Finally, an appraisal on the appropriate compositional gradient and utility of the heat treatment of the compositionally graded alloy is discussed in the context of specific requirements in structural applications.